Fetal strain and strain rate during pregnancy measured with speckle tracking echocardiography: A systematic review. - van Oostrum, Noortje H.M.; de Vet, Chantelle M.; van der Woude, Daisy A.A.; Kemps, Hareld M.C.; Oei, S. Guid; van Laar, Judith O.E.H. (European Journal of Obstetrics & Gynecology & Reproductive Biology, 2020)
Establishment of the maturational patterns of the fetal left and right ventricle strain and strain rate by two-dimensional speckle tracking echocardiography is a prerequisite for its routine clinical adaptation in pregnancy. The aim of this study is to review systematically current literature on the development of left and right ventricle strain and strain rate derived by speckle tracking during gestation. EMBASE, Medline and Central were searched, from inception to October 2019, for observational studies of singletons in uncomplicated, non-anomalous pregnancies, measuring global longitudinal strain and strain rate with 2D speckle tracking echocardiography in the fetal heart during gestation. 23 Studies met the inclusion criteria. The gestational age of the included fetuses varied from 12 to 42 weeks. Four studies used a longitudinal study design, with few consecutive measurements at varying gestational ages. 19 Studies performed either cross sectional or both longitudinal and cross sectional measurements. The ultrasound devices and speckle tracking algorithm software used, varied. Strain and strain rate during gestation increased, decreased or remained stable in the left and right fetal ventricle with increasing gestation. Due to considerable variation in the included gestational ages measured and inconsistency in the direction of strain and strain rate development, a meta-analysis could not be performed. Contradictory results concerning the development of strain and strain rate during gestation were shown, probably due to suboptimal study designs and varying algorithms and ultrasound devices used. A large longitudinal cohort study is needed to obtain reference values for fetal cardiac deformation in the uncomplicated, singleton pregnancy.